Influences of key stakeholders' involvement in maintenance management. Issue 2 (18th April 2017) - Au-Yong, Cheong Peng; Ali, Azlan-Shah; Ahmad, Faizah; Chua, Shirley Jin Lin
Abstract : Purpose: Proper maintenance management ensures a long-term investment and provides a support function in business continuity to achieve organisational goal. However, inadequate involvement and participation of key stakeholders in maintenance management limit the continuous improvement of maintenance performance. Currently, there is a lack of studies about the influence of key stakeholders' involvement in maintenance. Thus, the purpose of this paper is to deal with enhancement of maintenance management through the involvement of key stakeholders. Design/methodology/approach: This research adopted a mixed method approach to determine the relationship between involvement of key stakeholders in maintenance management and maintenance effectiveness. The approach comprised of literature review, questionnaire survey and semi-structured interviews. Findings: This research suggests a positive correlation between involvement of maintenance manager (MM), maintenance staff, organisation, user and maintenance service provider (SP) in improving the effectiveness of maintenance management. The logistic regression analysis indicated that the involvement of MM and SP are significant predictors of maintenance effectiveness. The research further identified that there was a lack of involvement of the user and SP in maintenance management. Originality/value: The research demonstrated that all key stakeholders should value the important roles of their participation in maintenance management to ensure an optimum return on a long-term investment. To create the awareness for the involvement of key stakeholders in building maintenance, studies on the advantages of participating in building maintenance and the impacts of ignorant towards building maintenance can be beneficial to the industry.